2016
DOI: 10.1080/15205436.2016.1187754
|View full text |Cite
|
Sign up to set email alerts
|

It Only Happens Once: Adolescents’ Interpretations of Mediated Messages About Sexual Initiation

Abstract: The current study examines adolescents' interpretations of a televised scene narrative describing a sexual initiation encounter. The study uses the media practice model (MPM) as a theoretical framework. Two hundred and ninety three 10 th -12 th graders suggested possible endings to the narrative, reflecting their outcome expectancies for sexual initiation. The adolescents' suggested scene endings were divided into ten different categories, including emotional, physical, and relational outcomes. A thematic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, in a study of adults, media was found to continue to portray a sexually objectified and unrealistically thin body ideal (Greenwood & Lippman, 2010). While adolescents consume, interact with, and make their own media, they are still shaped by and rely on it for messages about sex, gender roles, and relationships (Eyal & Ben-Ami, 2017; Hartley, Wight, & Hunt, 2014; Len-Ríos et al, 2016). In particular, one study found that 57% of adolescents, ages 14 to 16 years, identified media as an important source of sexual knowledge (A.…”
Section: Evidence For the Sexualization Of Girlsmentioning
confidence: 99%
“…In addition, in a study of adults, media was found to continue to portray a sexually objectified and unrealistically thin body ideal (Greenwood & Lippman, 2010). While adolescents consume, interact with, and make their own media, they are still shaped by and rely on it for messages about sex, gender roles, and relationships (Eyal & Ben-Ami, 2017; Hartley, Wight, & Hunt, 2014; Len-Ríos et al, 2016). In particular, one study found that 57% of adolescents, ages 14 to 16 years, identified media as an important source of sexual knowledge (A.…”
Section: Evidence For the Sexualization Of Girlsmentioning
confidence: 99%